The Albertina Sisulu Executive Leadership Programme enhancing the competencies and performance of public health service managers in South Africa. Issue 2 (13th February 2020) - Van der Berg-Cloete, Sophy Evelyn; Olorunju, Steve; White, John George; Buch, Eric
Abstract : Purpose: The purpose of this paper is to evaluate the effect of the Albertina Sisulu Executive Leadership Programme in Health (ASELPH) in improving the competencies and performance of public healthcare managers in South Africa (SA). Design/methodology/approach: This study used a quasi-experimental study design, with pre-post assessments to assess the performance and competencies of students participating in a public health leadership programme. Students were assessed using a 360° assessment of 14 competencies and 56 performance indicators. Findings: Students improved significantly in 11 competencies and 44 performance indicators; they perceived improvements in their own performance. The assessors observed the same improvements, which confirmed performance change at the students' workplaces. The study showed the positive effect of the ASELPH Fellowship in improving the competencies and performance of public healthcare managers in SA. Originality/value: The ASELPH Fellowship enhanced the leadership competencies and the performance of South African public healthcare managers. South African public healthcare managers face significant challenges and concerns have been raised regarding the competencies of healthcare managers to deal with these challenges. This study shows that leadership programmes can improve competencies and performance of managers to have an impact on the South African healthcare system